2020
DOI: 10.1016/j.ijfatigue.2019.105282
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian analysis of critical fatigue failure sources

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Specimens with larger critically loaded surface areas and volumes show decreased lifetimes compared to specimens with smaller critically loaded surfaces and volumes. This phenomenon is well-studied [71][72][73][74][75][76][77][78][79][80][81][82][83][84] and understood well enough to be included in design standards [85][86][87]. Ultrasonic fatigue specimens, i.e., all specimens used for very high strain rate fatigue tests, are generally small-sized.…”
Section: Extrinsic Effectsmentioning
confidence: 99%
“…Specimens with larger critically loaded surface areas and volumes show decreased lifetimes compared to specimens with smaller critically loaded surfaces and volumes. This phenomenon is well-studied [71][72][73][74][75][76][77][78][79][80][81][82][83][84] and understood well enough to be included in design standards [85][86][87]. Ultrasonic fatigue specimens, i.e., all specimens used for very high strain rate fatigue tests, are generally small-sized.…”
Section: Extrinsic Effectsmentioning
confidence: 99%
“…Through multiple fatigue tests on composite beams with partial shear connection structures, it is found that the fatigue stiffness calculation method is only based on the fitting of test data and the adaptability of the model has yet to be investigated [10]. In addition, a new calculation model was developed for the deformation behavior of steel-concrete composite beams under fatigue loading, taking into account the cross-sectional stiffness, pegging performance, load amplitude, and load ratio of the composite beam [11,12]. Jianjun has carried out many fatigue tests on composite beams with partial shear connections and deduced the calculation method of fatigue stiffness, but it is only based on the fitting of test data, so the adaptability of the model needs to be studied [10].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed model considered the cross-sectional stiffness of composite beams, stress performance of studs, load amplitude, load ratio, and other factors [11]. Composite beams are prone to fatigue failure when subjected to repeated vehicle loads [12]. Fatigue load will increase the slip at the interface between concrete and steel beam, and the increase of slip will reduce the stiffness of composite beam [13,14].…”
Section: Introductionmentioning
confidence: 99%